2016
DOI: 10.1097/mib.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Role of Altered Expression of miR-146a, miR-155, and miR-122 in Pediatric Patients with Inflammatory Bowel Disease

Abstract: Our results showed altered expression of miR-146a, -155, and -122 in the colonic mucosa of children with IBD and in TNF-α-treated colonic epithelial cells. Our data suggest the TNF-α-related involvement of these miRs in the pathogenesis of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 74 publications
0
52
0
Order By: Relevance
“…Among the commonly deregulated miRNAs, microRNA-375 was previously described as being up-regulated in serum from UC and CD patients 49 and in IL10 −/− mice 50 . Micro-RNA-122 is known to be increased in several inflammatory conditions 51, 52 , and was recently observed to be increased in uninvolved colonic mucosa of pediatric CD patients 53 and in colon biopsies during the progression from non-neoplasia to dysplasia in a group of 4 CD patients 54 , and downregulated in transition from dysplasia to cancer in this same group 54 . Finally, miRNA-150 was previously shown to be up-regulated in colonic tissues of DSS-induced colitic mice and UC patients 55 .…”
Section: Discussionmentioning
confidence: 88%
“…Among the commonly deregulated miRNAs, microRNA-375 was previously described as being up-regulated in serum from UC and CD patients 49 and in IL10 −/− mice 50 . Micro-RNA-122 is known to be increased in several inflammatory conditions 51, 52 , and was recently observed to be increased in uninvolved colonic mucosa of pediatric CD patients 53 and in colon biopsies during the progression from non-neoplasia to dysplasia in a group of 4 CD patients 54 , and downregulated in transition from dysplasia to cancer in this same group 54 . Finally, miRNA-150 was previously shown to be up-regulated in colonic tissues of DSS-induced colitic mice and UC patients 55 .…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, upregulation of miR‐146b‐5p is associated with cell proliferation, aggressiveness, and poor prognosis as an oncogene in papillary thyroid carcinoma, lung cancer, and gastrointestinal malignant tumour . In IBD, miR‐146a expression was elevated in the colonic mucosa of both paediatric and adult patients compared to in healthy controls . Peck et al also found that miR‐146b‐5p was upregulated in colonic RNA‐sequencing data of patients with CD and in healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…Given the potential relationship between FOXP3 and miR-31 ( Figure 5), it is unsurprising to find that miR-31 is dysregulated in several autoimmune diseases such as IBD or Crohn's disease 85,86 and Kawasaki disease. 87 Therefore, understanding the molecular mechanisms by which FOXP3 and miR-31 regulate each other, and identifying the target genes within this regulatory network, could contribute to the development of novel treatments for autoimmune disease.…”
Section: Foxp3 Cooperates With Micrornas Via Regulatory Loops Which Tmentioning
confidence: 99%